Autopercepção da qualidade de vida e sua relação com discrepâncias maxilo-mandibulares, variáveis clínicas e terapia de reposição enzimática em pacientes com mucopolissacaridose na cidade de Fortaleza, Brasil - Costa, Renata Torreão Viana de Melo (2023)
Mucopolysaccharidoses (MPS) are a group of rare inherited diseases caused by a deficiency of lysosomal enzymes in glycosaminoglycan (GAG) catabolism. The study evaluated the self- perception of quality of life (QoL) of patients affected by mucopolysaccharidoses (MPS) and its relationship with maxillomandibular discrepancies, clinical variables, and enzyme replacement therapy (ERT). This is a cross-sectional study paired by gender and age. Participants answered the sociodemographic questionnaire, medical history, and World Health Organization Quality of Life – BREF (WHOQOL-BREF) or Autoquestionnaire Qualité de Vie Enfant Imagé (AUQEI) instruments, validated in Portuguese; and were clinically evaluated for the presence of maxillomandibular discrepancies. For internal consistency of the instruments, Cronbach's alpha coefficient, WHOQOL-BREF (0.84) and AUQEI (0.99) were used. Data were expressed in descriptive statistics. The chi-square and/or Fisher's exact test evaluated the association of variables with facets/domains; Spearman's test, correlations; while the Mann Whitney or Kruskal-Wallis/Dunn test, data comparison. The adopted statistical significance level was 5% (p < 0.05) and the 95% confidence interval. A sample of 26 MPS patients (15.23 ±9.01 years; female: n=10, 38.5%; male: n=16, 61.5%) participated in the research. In the WHOQOL-BREF, the MPS group scored lower in all domains compared to the control group, with a lower score in the physical health domain. There was a significant association between family income and home environment (p = 0.016). In the AUQEI, there was a statistically significant difference between the mean QL of the MPS group and the control group, both in the domain of autonomy (p = 0.035) and in the GLOBAL QL (p = 0.001), both with satisfactory QL. However, the MPS group showed a lower average in the autonomy domain and showed an association between sagittal alteration and the function domain (p = 0.020). MPS patients presented a self-perception of reduced QoL when compared to the control group, demonstrating that the establishment of an earlier intervention through enzymatic therapy and clinical follow- up measures can interfere in the maxillomandibular development with the aim of reducing the craniofacial alterations of these patients over time. over the years, being able to help improve QoL.